The Principles of Educational Leadership in the Perspective of the Qur’an - Assa'idi, Sa'dullah; Hamid, Abd.; Subaidi, Subaidi (IAIN Samarinda, 2021)
Humans as inheritors of the earth regulate life and everything. With their intellects and skills, they can make the earth a place to carry out various daily activities. As the caliphs, they get the trust that must be implemented on the earth. In this study, the authors would adopt the cornerstone principles of leadership education in general and in view of the Quran. Principles of leadership in general education studied were those of integrative and cooperative capacity, rationality and objectivity, adaptability and flexibility, delegation, pragmatism, and exemplary. On average, the principles of educational leadership in the perspective of the Qur'an are the principle of tawhid, deliberation, fairy, freedom, upright, commanding the good and forbidding the evil, and a good example. From these two principles of educational leadership, they include the education for a leader who according to the morality of the Qur'an (1) is tolerant, (2) likes to do deliberation in decision-making, (3) is fair in terms of law, (4) gives freedom, (5) can be trusted, (6) is always doing good, and (7) gives good examples. An educational leader as stated in the Qur'an is the one who upholds Islamic values and leadership principles.